Study of thrombin generation with St Genesia to evaluate xaban pharmacodynamics: Analytical performances over 18 months. (28th December 2020) - Foulon‐Pinto, Geoffrey; Jourdi, Georges; Perrin, Julien; Abdoul, Johan; Paris, Guillaume; Gouin‐Thibault, Isabelle; Curis, Emmanuel; Lecompte, Thomas; Siguret, Virginie
Abstract: Introduction: ST Genesia is a new automated system enabling quantitative standardized evaluation of thrombin generation (TG), for example, in patients receiving anti‐Xa direct inhibitors (xabans). Data on its analytical performances are scarce. Methods: Over an 18‐month period, repeatability, reproducibility, and accuracy were assessed using STG‐ThromboScreen (without or with thrombomodulin) or STG‐DrugScreen reagents (corresponding to intermediate/high tissue‐factor concentration, respectively), and controls. Furthermore, reproducibility was assessed using commercialized lyophilized and frozen normal pooled plasmas. Rivaroxaban and apixaban impacts on TG parameters were assessed using spiking experiments. Finally, a comparison with the Calibrated Automated Thrombogram method (CAT) (PPP reagent) was performed using plasma from healthy volunteers enrolled in the DRIVING‐studyNCT 01627665) before and after rivaroxaban intake. Results: For all dedicated quality control (QC) levels, inter‐series coefficients of variations (CV) were <7% for temporal TG parameters, peak height (PH), and endogenous thrombin potential (ETP), whether results were normalized with a dedicated reference plasma STG‐RefPlasma or not. Noteworthy, STG‐RefPlasma used for normalization displayed substantially high PH and ETP. Mean biases between the observed and manufacturer's assigned QC values were mostly <7%. Both rivaroxaban/apixaban plasma concentrations were significantly associated with TG parameters. Finally, Bland‐Altman plots showed a good agreement between ST Genesia‐STG‐ThromboScreen and CAT method within the explored range of values, although biases could be observed (PH: 16.4 ± 13.2%, ETP: 17.8 ± 11.9%). Conclusion: ST Genesia ® enables the reliable measurement of TG parameters in both in vitro and ex vivo xaban plasma samples using either STG‐ThromboScreen or STG‐DrugScreen according to xaban concentrations. The use of reference plasma, despite not completely reflecting a normal pooled plasma behavior, likely improves standardization and inter‐laboratory comparisons.